David Novak : natural law and revealed Torah - Tirosh-Samuelson, Hava, 1950-; Hughes, Aaron W., 1968- (Library of Contemporary Jewish Philosophers, 2013)
This volume features the thought and writings of Rabbi David Novak, the J. Richard and Dorothy Shiff Chair of Jewish Studies, Professor of the Study of Religion, and Professor of Philosophy at the University of Toronto. Novak is a leading Jewish theologian, ethicist, and scholar of Jewish philosophy and law. Natural Law and Revealed Torah presents the work of Novak, a thinker interested in the intersection of traditional Judaism and the modern world, especially how religious Jews can simultaneously exist within the liberal and democratic nation state yet remain separate from its tradition of secularism. This volume is also available in paperback .